The Efectiveness Of Picture Prompt In Teaching Descriptive Text - Casimirus Andy Fenanlampir (Universitas Musamus, Merauke, Papua, 2020)
Picture prompt is media combination pictures and clues. This study was conducted to find out the effectiveness of picture prompt as a media to improve students’ ability in writing descriptive text. This used an experimental method. Based on the test scores in the pre-test and post-test, there were significant developments. This can be seen in the percentage value of each test. The percentage of the post-test was 58.1% in the control class and then the post-test developed to 79.03% in the experimental class. It is implied that using pictures with instructions can develop the students’ writing descriptive text ability. Therefore, students are able to express themselves creatively and cogently. Keywords: picture prompt, writing, descriptive text